Kinetic and equilibrium modeling for removal of nitrate from aqueous solutions and drinking water by a potential adsorbent, hydrous bismuth oxide - Singh P.K.; Banerjee S.; Srivastava A.L.; Sharma Y.C. (My University, 2025)
The kinetic, equilibrium modeling and adsorption characteristics of hydrous bismuth oxides (HBOs) have been investigated for the removal of nitrate from aqueous solutions. The three HBO samples, designated as HBO1, HBO2 and HBO3 were synthesized by a controlled precipitation method. Among three HBO samples, HBO3 accounts for a maximum nitrate uptake of 0.22 mg N g-1 with an initial nitrate concentration of 14 mg N L-1, therefore this was selected for detailed studies. HBO3 was characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy and energy dispersive spectrometry. The adsorption characteristics and process variables were investigated by examining different parameters such as pH, contact time, initial nitrate concentration and temperature. Solution pH remarkably influences the nitrate sorption process as the sorption capacity was found to increase from 0.056 to 0.22 mg N g-1 with the increase of pH from 2.0 to 7.0. The sorption capacity was also found to increase with increasing concentration and temperature, while the presence of competing anions such as Cl-, HCO3- and SO42- impeded the nitrate sorption capacity. The sorption kinetic data were found to be consistent with a pseudo-first-order kinetic model. The equilibrium data agree well with Freundlich model and the highest monolayer adsorption capacity of HBO3 for removal of nitrate ions was found to be 0.97 mg N g-1 at 313 K. An investigation of the thermodynamic parameters indicated the spontaneous and endothermic nature of the sorption process. In a nutshell, HBO3 shows significant potential for removal of nitrate ions from aqueous solution as well as drinking water. © The Royal Society of Chemistry 2015.